2023
DOI: 10.4111/icu.20220411
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of artificial intelligence-based decision supporting system in tolvaptan prescription for autosomal dominant polycystic kidney disease

Abstract: Purpose Total kidney volume (TKV) measurement is crucial for selecting treatment candidates in autosomal dominant polycystic kidney disease (ADPKD). We developed and investigated the performance of fully-automated 3D-volumetry model and applied it to software as a service (SaaS) for clinical support on tolvaptan prescription in ADPKD patients. Materials and Methods Computed tomography scans of ADPKD patients taken between January 2000 and June 2022 were acquired from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Consequently, the height-adjusted TKV (htTKV) and its annual rate of change have become primary endpoints in evaluating the treatment efficacy in clinical trials. Recent strides in artificial intelligence (AI) have enabled rapid and reproducible automated TKV measurements [5][6][7][8][9]. However, efforts to integrate TKV evaluation into clinical practice remain limited, as indicated by the PKD Foundation's 2022 survey, which revealed that 69% of patients had never undergone TKV measurements, and in those who had, the volume was measured predominantly for research purposes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the height-adjusted TKV (htTKV) and its annual rate of change have become primary endpoints in evaluating the treatment efficacy in clinical trials. Recent strides in artificial intelligence (AI) have enabled rapid and reproducible automated TKV measurements [5][6][7][8][9]. However, efforts to integrate TKV evaluation into clinical practice remain limited, as indicated by the PKD Foundation's 2022 survey, which revealed that 69% of patients had never undergone TKV measurements, and in those who had, the volume was measured predominantly for research purposes [10].…”
Section: Introductionmentioning
confidence: 99%